SANKSI KEBIRI KIMIA KEPADA PELAKU KEJAHATAN SEKSUAL TERHADAP ANAK - Farhan, Muhammad (Yayasan Daarul Huda Kruengmane, 2021)
This study aims to determine the regulation of chemical castration sanctions for perpetrators of sexual violence against children and legal protection related to the imposition of chemical castration sanctions on perpetrators of child sexual crimes. This study uses a normative juridical research method with a statutory approach. The nature of this research is descriptive analytical. The collection of legal materials is carried out by literature studies and data analysis techniques are carried out qualitatively. The results of this study indicate that chemical castration is one of the government’s effort which is believed to be able to anticipate sexual crimes against children and can provide a deterrent effect to perpetrators. But the fact is that since chemical castration was legalized until now it has not been able to prevent many cases of sexual crimes against children. Human Rights protection against the imposition of chemical castration sanctions for perpetrators of sexual crimes against children is contained in National and International legal instruments. In the National legal instruments, namely Article 28G Paraghraph (2) and Article 28I Paraghraph (1) of the 1945 Constitution, as well as Article 33 Paraghraph (1) of Law No.39 of 1999. While in International instrument it is contained in Article 5 of the Universal Declaration of Human Rights and Article 5 International Covenant on Civil and Political Right.